Taxonomic and phylogenetic study of the genus Lecaimmeria (Lecideaceae, Ascomycota) reveals two new species from Pakistan - Muhammad Shahid Iqbal; Muhammad Usman; Riaz Ullah; Abdul Nasir Khalid (Italian Journal of Mycology, 2025)
Two new species, Lecaimmeria pallidobrunnea sp. nov. and L. sultanii sp. nov. from Gilgit-Baltistan (Pakistan) are described here. A comparative morpho-anatomical, chemical and molecular based analyses confirmed the positions of both species within the genus Lecaimmeria. For molecular analyses ribosomal ITS and LSU regions were sequenced. Lecaimmeria pallidobrunnea differs from its closely related species, L. asiatica, by having hyaline conidiophores, pale brown to blackish brown or gray upper surface, grayish black to brownish black prothallus and growing on calcareous rocks in cold, semi-arid environment. Lecaimmeria sultanii differs from its closely related species, L. crispula, by having brownish gray to light black or dark gray upper surface, visible grayish black prothallus between areoles, apothecia 1–3 per areole, grayish brown to reddish brown apothecial disc, smaller epihymenium 10–20 µm, smaller hypothecium 50–90 µm, smaller ascospores 13–23 × 10–15 µm and growing on calcareous rocks.